Community Perception and Participation in Mangrove Ecosystem Restoration Effort in Lembar Village, West Lombok Regency - Sukuryadi Sukuryadi; Harry Irawan Johari (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
The mangrove ecosystem in the Lembar area has a high ecological role and is used as a pilot area for mangrove conservation and rehabilitation activities in the southern part of West Lombok Regency. Community perception and participation will determine the success of conservation and rehabilitation activities. Therefore, this study aims to determine and describe the perceptions and participation of the community in efforts to restore the mangrove ecosystem in Lembar Village, West Lombok. The research method was carried out through a qualitative research approach with the technique of determining the informant based on the purposive sampling technique. The results showed that community participation in mangrove ecosystem restoration efforts in the Lembar area of West Lombok as a whole showed a low category, this was caused by the characteristics of the community who did not have good knowledge and understanding of the mangrove ecosystem and the benefits of its development. The community's perception of the existence of the ecosystem and its development is categorized as low so that it has an impact on the low level of community participation in efforts to restore mangrove ecosystems.